Entacapone: improving aqueous solubility, diffusion permeability, and cocrystal stability with theophylline - Bommaka, Manish Kumar; Mannava, M. K. Chaitanya; Suresh, Kuthuru; Gunnam, Anilkumar; Nangia, Ashwini (Crystal Growth & Design, 2018)
Cocrystallization is a well-established technique to improve the solubility, bioavailability, and stability of active pharmaceutical ingredients (APIs) but permeability and diffusion rate control via cocrystals is relatively less well studied, and the exact role of coformers in influencing the diffusion rate of drug cocrystals is still not fully understood. The aqueous solubility and permeability diffusion of Entacapone, ETP, a Biopharmaceutical Classification System (BCS) Class IV drug of low solubility and low permeability, with Generally Regarded as Safe (GRAS) coformers has been studied. Fixed stoichiometry cocrystals of ETP with acetamide (ACT, 1:1), nicotinamide (NAM, 1:1), isonicotinamide (INAM, 1:1), pyrazinamide (PYZ, 1:1), and isoniazid (INZ), 1:1) were prepared by solvent-assisted grinding. Theophylline (THP) resulted in a cocrystal hydrate (ETP-THP-FIYD 1:1:1). The cocrystals were structurally characterized by single crystal and powder X-ray diffraction, DSC and TGA thermal measurements, and IR and NMR spectroscopy. Solubility and dissolution rate showed that there is a correlation between cocrystal stability and solubility governed by the heteromeric N-H center dot center dot center dot O, O-H center dot center dot center dot N, and O-H center dot center dot center dot O hydrogen bonds and conformational changes of ETP in cocrystal structures. ETP-THP-HYD and ETP-PYZ exhibit faster dissolution rate and high solubility and they are stable in phosphate buffer medium compared to the other cocrystals which dissociate partially during solubility experiments. Diffusion rates in a Franz cell showed that the stable and high solubility ETP-THP-HYD cocrystal has good permeability. Given that stability, solubility, and permeability are in general inversely correlated, the entacapone-theophylline hydrate cocrystal is a unique example of the thermodynamically stable cocrystal exhibiting high solubility and high permeability.

Enhanced solubility, permeability, and tabletability of nicorandil by salt and cocrystal formation - Mannava, M. K. Chaitanya; Gunnam, Anilkumar; Lodagekar, Anurag; Shastri, Nalini R.; Nangia, Ashwini K.; Solomon, K. Anand (Crystengcomm, 2021)
Cocrystallization is a rational selection crystal engineering approach for the development of novel solid forms with enhanced physicochemical and mechanical properties. Nicorandil (NCR) is a niacinamide vitamin derivative used to treat angina pectoris. A binary solid form screen of NCR with homologous dicarboxylic acids afforded NCR-oxalic acid (NCR-OA, 1:1), NCR-fumaric acid (NCR-FA, 1:1), NCR-succinic acid (NCR-SA, 1:1), and NCR-suberic acid (NCR-SBA, 1:0.5). The binary solids were characterized by powder X-ray diffraction, IR and NMR spectroscopy, and DSC. NCR-FA and NCR-SBA were crystallized by slow evaporation from chloroform and toluene solvents, respectively. Single crystal X-ray diffraction confirmed that NCR-FA is a molecular salt, while NCR-SBA is a neutral cocrystal. NCR and the FA anion are connected via the robust carbovlate-pyridinium synthon, whereas in the NCR-SBA cocrystal, the components associate via the carboxylic acid- -pyridine synthon. The phase stability, solubility, dissolution rate, diffusion rate and tabletability studies have demonstrated that the binary solids exhibit improved physical and mechanical properties compared to the NCR drug. Specifically, the NCR-FA salt and NCR-SBA cocrystal have higher solubility, dissolution rate, and hardness at lower pressures, making the formulation suitable for tablet compression.

Entacapone polymorphs: crystal structures, dissolution, permeability, and stability - Bommaka, Manish Kumar; Mannava, M. K. Chaitanya; Rai, Sunil K.; Suresh, Kuthuru; Nangia, Ashwini K. (Crystal Growth & Design, 2021)
Entacapone (ETP) is a catechol-O-methyltransferase (COMT) drug used to treat Parkinson's disease. ETP is available in the marketplace under the brand name Comtan since 2010, and ETP form-I was first reported in a patent published in 2001. However, analysis of its Xray crystal structures and stability relationship of ETP polymorphs and their dissolution and permeability profile have not yet been reported. We crystallized two new conformational polymorphs of ETP from a water and acetone mixture and studied the structural origin of polymorphism and their phase transformations, stability, equilibrium solubility, dissolution, and permeability properties. The ETP molecule adopts different conformations in the polymorphic structures with slight changes in carbonyl and nitrile group orientations. Thermal analysis suggests that form-III and form-IV are enantiotropically related to form-I, which is the thermodynamically stable form at ambient conditions. In contrast, form-II is monotropically related to form-I. Equilibrium solubility, dissolution, and permeability studies show that form-II persists in the slurry medium and dissolves faster with a high flux rate compared to the stable form-I in phosphate buffer solution at 37 +/- 0.5 degrees C.